Challenges in Literature Learning in Secondary Education (Journal SCIENCEVOLUTION, 2025)
This qualitative study is a bibliographic review of the challenges in learning literature in secondary education, which applied a hermeneutic analysis method, with the objective of detecting the pedagogical barriers, methodologies and other limitations of the educational contexts faced by teachers and students. Based on findings from reliable global research, PISA, and regional research, ERCE, which show the low performance in reading comprehension of students in Latin America and the Caribbean, especially in the Dominican Republic. The role of teachers, their training, reading attitudes and beliefs have an impact on student learning. Also, the reading processes were investigated, considering cognitive, affective, cultural and economic elements, and the importance of implementing pedagogical strategies to promote meaningful reading is highlighted. On the other hand, the use of active methodologies, such as gamification, collaborative work, sensory learning and the use of technology is emphasized. However, considerable challenges were detected, such as lack of resources, resistance to change in educational methodologies, decontextualization of didactic materials and insufficient training programs.
Keywords: Literature; Didactics; Reading comprehension; Pedagogical strategies